TANAMAN KANGKUNG HIDROPONIK DAN KAMPUNG WARNA - Sugeng Hadi Purnomo (JPM17: Jurnal Pengabdian Masyarakat, 2017)
Hydroponics is also known as the cultivation of plants without media. Hydroponiccultivation does not require a large area. Provided that the fulfillment of nutritionalneeds for the relevant plants are met and enough sunlight, then one can already growcrops using hydroponics as a medium. Since the area of RW06 and RW12 Putat JayaSub-District of Sawahan District formerly Dolly's ex-localization area ("Dolly Gang")is made up of many gangs, and each gang connects with other smaller gangs, hencehydroponic cultivation Suitable to apply there. In addition we also changed the EastKupang Gang Gang in RT05, RW06, Putat Jaya Village, Sawahan Sub-Districtbecame more colorful. Keywords: Putat Jaya, Kangkung Hydroponik, Kampung Warna, Untag Students,KWU Division, Gang Dolly.